INTEGRASI NILAI NILAI KEISLAMAN DALAM PROSES PEMBELAJARAN DI FAKULTAS TARBIYAH DAN ILMU KEGURUAN UIN SYAHADA PADANGSIDIMPUAN - Melati Sukma Aulia Saragih; Indah Suryani; Mila Sari (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2026)
The integration of Islamic values into the learning process is an essential effort in shaping student character within Islamic higher education institutions, including the Faculty of Tarbiyah and Teacher Training at UIN Syahada Padangsidimpuan. This study was conducted to obtain an overview of how Islamic values are internalized throughout academic activities so that they do not remain merely theoretical concepts. The research employed a qualitative approach with a descriptive method through observation, interviews, and documentation involving lecturers and students. The findings indicate that Islamic values are integrated through lecturers’ exemplary behavior, the habituation of religious academic culture, the embedding of moral principles in course materials, and the creation of a learning environment that supports Islamic character development. These results show that the integration of Islamic values contributes to increased learning motivation, discipline, and students’ sense of responsibility. Based on these findings, the study concludes that the integration process has been implemented effectively, although strengthening is still needed in terms of consistency and continuous evaluation.